Cardiovocal Syndrome (Ortner's Syndrome) Associated with Chronic Thromboembolic Pulmonary Hypertension and Giant Pulmonary Artery Aneurysm: Case Report and Review of the Literature. (14th October 2012) - Heikkinen, Jaakko; Milger, Katrin; Alejandre-Lafont, Enrique; Woitzik, Christian; Litzlbauer, Detlef; Vogt, Julia-Franziska; Klußmann, Jens Peter; Ghofrani, Ardeschir; Krombach, Gabriele A.; Tiede, Henning
Abstract : Cardiovocal syndrome or Ortner's syndrome is hoarseness due to left recurrent laryngeal nerve palsy caused by mechanical affection of the nerve from enlarged cardiovascular structures. Chronic thromboembolic pulmonary hypertension is extremely rarely found to cause this syndrome. We describe a case of a 56-year-old patient with sudden onset of hoarseness. The patient had known long standing severe pulmonary hypertension. Fiberoptic laryngoscopy showed left vocal cord palsy. Computed tomography of the neck and chest revealed extensive enlargement of the pulmonary arteries and excluded a malignant tumor. The diagnosis of cardiovocal syndrome was retained. It is important for the radiologist to be aware of this possible etiology causing left recurrent laryngeal nerve palsy and to understand its mechanism.